Art and play: a necessary inter-relationship in pandemic times: uma inter-relação necessária em tempos de pandemia - Camargo, Janete Santos da Silva Monteiro de (Revista do Colóquio, 2020)
Abstract: The theme of this research arose from pedagogical experiences carried out remotely. This investigation intends to emphasize the importance of playing and its interrelation with Art and also to analyze data collected on the favorite games of the responsible and of the children researched. The praxis took place in the discipline of Art, with one hundred and eighty students, from the seventh year, from elementary school II, from a public school. We use the methods of literature review and qualitative and quantitative research. In the results we verified that some games passed through generations, while others did not last. We conclude that the interrelationship between art and play is important and necessary, especially in the context we are living in, thus promoting relaxation and interaction between families.